The application of new industrial maintenance concepts - an easy way to saving money - Veronica Banciu, Felicia; Pamintas, Eugen; Ioana, Anamaria (Journal of Production Engineering, 2023)
Since the beginning of the current millennium, various professional organizations, research institutes, scientific papers in journals and various conferences around the world, address the issue of maintenance, generically speaking, both theoretically, directly or tangentially and by examples of benefits in industry for various production processes, machines and installations. However, recent studies and reports reveal that even in highly industrially developed countries, company management aims to improve maintenance in only about 15% of cases for the next plan year. Why, this is the question? This paper will try to provide answers and even propose possible solutions to increase the applicability in industry of new concepts and theories of maintenance. The arguments used are less oriented on the technical side, they are mainly focused on the “money” indicator, close to the understanding of the company’s senior management, i.e. on how huge material benefits can be obtained compared to the insignificant investment expenses.